The impact of unemployment and income on delinquency and default in the USA - Mateus, Joana Beatriz Lourenço (2020)
This investigation focuses on the impact of unemployment and income on delinquency and default rates. Auto loans, credit cards, mortgages and student loans in the United States of America (USA) were used to perform this analysis Panel data covered the District of Columbia and the 50 states of the USA with annual data from 2003 to 2018. A probit model was used and compared with a linear model for each type of loan. The innovation of this study is the introduction of the spread of unemployment variable to study the effect of unemployment on these loans’ delinquency rates. This study finds empirical evidence that the spread of unemployment increases delinquency and default on credit, and the median household income decreases the delinquency and default in the USA. The results demonstrate that consumer sentiment impacts negatively on delinquency and default, as does the S&P 500 index. To prevent the effects of delinquency and default on the economy, the US government should promote measures to create more jobs, reducing unemployment and increasing household income.